2021
DOI: 10.1021/acsaem.1c01540
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo Leaves as Sustainable Sources for the Preparation of Amorphous Carbon/Iron Silicate Anode and Nickel–Cobalt Silicate Cathode Materials for Hybrid Supercapacitors

Abstract: The design and discovery of sustainable electrode materials with outstanding capacitance for energy storage from environmentally friendly biomass as the raw material are a task filled with challenges and opportunities. In this work, we demonstrate that the hybrid supercapacitor (HSC) device is assembled by metal silicates for the first time. The amorphous carbon/iron silicate (C/Fe 24 Si 4 O 43 (OH) 2 , denoted as C/FeSi) anode and cobalt−nickel silicate (Co x Ni 2−x SiO 4 , denoted as CoNiSi) cathode material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 63 publications
(153 reference statements)
0
17
0
Order By: Relevance
“…Supercapacitors have received considerable attention in the field of energy storage because of their high power densities, fast charging/discharging rates, and long life cycles. , Supercapacitor electrodes can be classified into three types depending on their energy-storage mechanism: electric double-layer capacitors (EDLCs), pseudocapacitors, and hybrid electrodes. , EDLCs, which are based on the physical accumulation of charged species on the electrode surface, have a high power density; however, their energy density is low. , Carbon-based materials are commonly used for fabricating EDLC electrodes because of their large specific surface area (SSA) and superior electrical conductivity. , Among them, graphene has attracted interest owing to its excellent electrical conductivity with a large SSA . Pseudocapacitors, which store energy through surface redox or Faradaic reactions, exhibit higher energy densities than EDLCs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supercapacitors have received considerable attention in the field of energy storage because of their high power densities, fast charging/discharging rates, and long life cycles. , Supercapacitor electrodes can be classified into three types depending on their energy-storage mechanism: electric double-layer capacitors (EDLCs), pseudocapacitors, and hybrid electrodes. , EDLCs, which are based on the physical accumulation of charged species on the electrode surface, have a high power density; however, their energy density is low. , Carbon-based materials are commonly used for fabricating EDLC electrodes because of their large specific surface area (SSA) and superior electrical conductivity. , Among them, graphene has attracted interest owing to its excellent electrical conductivity with a large SSA . Pseudocapacitors, which store energy through surface redox or Faradaic reactions, exhibit higher energy densities than EDLCs .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Supercapacitor electrodes can be classified into three types depending on their energy-storage mechanism: electric double-layer capacitors (EDLCs), pseudocapacitors, and hybrid electrodes. 3 , 4 EDLCs, which are based on the physical accumulation of charged species on the electrode surface, have a high power density; however, their energy density is low. 3 , 5 Carbon-based materials are commonly used for fabricating EDLC electrodes because of their large specific surface area (SSA) and superior electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported biomass obtained from bamboo leaves with metal silicates showed specific energy density of 6.55 Wh kg −1 and power density of 68.36 W kg −1 . [ 51,52 ] These results indicate that both the specific energy density and specific power density in this PDI‐Py/GF//PDI‐Py/GF SSC are highly competitive. The SC performance of this cell can be attributed to a large increase in active behavior of PDI‐Py in Faradaic redox reaction, suggesting the potential application of organic materials in enhancing the electrochemical performance.…”
Section: Resultsmentioning
confidence: 87%
“…The binding energy separation is 13.6 eV, manifesting the characteristic peak of Fe 2+ in ferric silicate. [ 40 ] The corresponding satellite peaks locate at 716.3 and 729.8 eV, respectively. [ 41,42 ] Si 2 p peak centered at 102.5 eV indicates the formation of FS rather than the mixture of FS and SiO 2 , for Si 2 p in SiO 2 centered at the binding energy is more than 103 eV (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%